Pemanfaatan Bonggol Pisang Dan Kulit Kacang Tanah Sebagai Bahan Baku Plastik Biodegradable dengan Penambahan Gliserol - Amelia, Risky; , Dra. Aminah Asngad, M.Si (2017)
Biodegradable plastic is a environmentally friendly plastics which can hang loosly by activity of chemicals micro-organism. In the manufacture of biodegradable plastics, the main material is required in the form of starch. Flour banana's corm can be used to make biodagradable plastic because it contains starch which is quite enaugh. In the manufacture of biodegradable plastics it is needed increasing natural cellulose and glycerol for repair physical characteristic and mechanical plastic. The aim of this study, wasto find out mechanical characteristic (tensile strength and elongation strenght) and biodegradability strength of biodegradable plastic with increasing peanuts leather and glycerol. This study used an experimental method of Completely Randomized Design (CRD) by two factorial, namely: comparision flour banana's corm concentration with peanut leather, the first factor namely: 8.5g:1.5g, 9g:1g, 9.5g:0.5g and the secon factor was glycerol volume, namely: 6ml, 7ml, 8ml. The data result of analyzing observation was by using descriptive qualitative. The result of this study showed that highest of Tensile strange in banana's corm-peanuts leather(8.5:1.5)-glycerol 6 ml worth 1.62 N/mm2, the highest of elongation strange (9:1)-glycerol 7 ml worth 21.33%. Most excellent biodegradability test result in treatment use 8ml glycerol with residual weight of 9.617%.